2015
DOI: 10.1111/jgh.12831
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of natural resistance mutations in naïve chronic hepatitis B patients: A systematic review and meta‐analysis

Abstract: The resistance mutations occurred frequently in untreated CHB patients, especially in China. The lamivudine resistance had the highest natural prevalence rate, while other nucleos(t)ide analogues showed rarely spontaneous resistance. Detecting the spontaneous resistance mutations will benefit the clinical management of CHB patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 50 publications
1
45
1
Order By: Relevance
“…They found genotype C HBV infection, male, and HBeAg negative patients had a slightly higher natural mutation rate when compared with genotype B and D HBV infection, female, and HBeAg positve patients. The ALT serum levels showed no influence on the emergence of antiviral resistance mutations 44. In Brazil, there are few studies that were conducted on survey resistance mutations to NA on naïve patients seeking clinical association 4547.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…They found genotype C HBV infection, male, and HBeAg negative patients had a slightly higher natural mutation rate when compared with genotype B and D HBV infection, female, and HBeAg positve patients. The ALT serum levels showed no influence on the emergence of antiviral resistance mutations 44. In Brazil, there are few studies that were conducted on survey resistance mutations to NA on naïve patients seeking clinical association 4547.…”
Section: Discussionmentioning
confidence: 93%
“…However, Zhang et al44 conducted a meta-analysis to apprise the incidence of natural resistance mutations in naïve chronic hepatitis B patients. They found genotype C HBV infection, male, and HBeAg negative patients had a slightly higher natural mutation rate when compared with genotype B and D HBV infection, female, and HBeAg positve patients.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta‐analysis of the prevalence of HBV‐DR variants from 106 studies involving 12 212 patients with chronic HBV infection who had not received prior NUC therapy found that the global prevalence of all mutations (primary and secondary) was 5.7%, 5.4% for primary and 2.9% for secondary HBV‐DR variants . There was significant geographical variation with the highest prevalence in China where the pooled prevalence rate of primary and secondary DR variants based on >8000 patients was 8% (95% CI 6.63‐9.38) while the pooled prevalence rate in other countries was 1.9% (95% CI 1.06‐2.69).…”
Section: Discussionmentioning
confidence: 99%
“…This is of most concern in countries where NUCs with low barrier to resistance are frequently used as first‐line therapy. A meta‐analysis of 106 studies examining the prevalence of HBV‐DR variants in 12 212 persons with chronic HBV infection who had never received NUCs found an overall prevalence of 5.73% (95% confidence interval [CI]: 4.85%‐6.61%); however, there were wide geographical variations ranging from 20% in Africa to 0% in Brazil . An important reason for the wide range in results is differences in sensitivities of assays used to detect DR variants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation